The role of leadership and values in creating a positive organisational culture - van der Walt, F.; Wiese, L. (South African Journal of Higher Education, 2025)
South African Higher Education institutions have historically faced significant challenges which hindered the establishment of a genuinely inclusive and conducive organisational culture. This study aimed to explore the organisational culture of a university of technology and consider the role of institutional leadership and organisational values in shaping a positive organisational culture within the university. This study utilised a case study design and a document analysis was conducted. The document analysis revealed sub-themes related to leadership, such as high leadership turnover, lack of information sharing, male-dominant leadership, lack of alignment between leadership structures, and student leadership. In terms of values, it became evident that values and culture are not aligned, employees lack knowledge of values, are not living organisational values, values are absent in Human Resources systems, and concerns were raised regarding student values. The study contributed to organisational culture literature in the Higher Education domain which is currently lacking.